Pengaruh Kepemimpinan Kepala Madrasah dan Lingkungan Kerja Terhadap Kinerja Guru di MTS Kabupaten Solok Wilayah Selatan - Putra, Varizki Syaf; Aprison, Wedra (Universitas Syiah Kuala, 2025)
In this research, the author uses a quantitative approach with a correlation research type. The data analysis technique uses simple linear regression and multiple linear regression. The sampling technique in this research used Probability Sampling with a sample size of 133 out of 205 populations. The model chosen was simple random sampling, the data collection technique used a questionnaire, then analyzed using the Anova test with the help of SPSS 2020. The findings from the research day were as follows: 1) Based on the results (tcount ttable) with a tcount value of 6.064 and ttable amounting to 1,978. The influence of madrasa head leadership on teacher performance in Solok Regency, Southern Region is 21.9%. 2) Based on the results (tcount ttable) with a tcount value of 5.424 and ttable of 1.978. The influence of the work environment on the performance of student teachers in Solok Regency, Southern Region is 18.3%. 3) Based on the results (Fcount Ftable) with a Fcount value of 29.999 and Ftable 3.07. At an error level of 5%, the significance level is 0.000 0.05, then the leadership of the madrasa head and the work environment together have an effect on teacher performance in Solok Regency, Southern Region, by 31.0%.